2018
DOI: 10.48550/arxiv.1812.08405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On nonlinear Schrödinger equations with repulsive inverse-power potentials

Abstract: In this paper, we consider the Cauchy problem for the nonlinear Schrödinger equations with repulsive inverse-power potentialsWe study the local and global well-posedness, finite time blow-up and scattering in the energy space H 1 for the equation. These results extend a recent work of Miao-Zhang-Zheng [Nonlinear Schrödinger equation with coulomb potential, arXiv:1809.06685] to a general class of inverse-power potentials and higher dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The proof is based on the interaction Morawetz inequality. A similar result for the repulsive inverse-power potentials was established in [13]. Let us start with the following classical Morawetz inequality.…”
supporting
confidence: 60%
“…The proof is based on the interaction Morawetz inequality. A similar result for the repulsive inverse-power potentials was established in [13]. Let us start with the following classical Morawetz inequality.…”
supporting
confidence: 60%
“…This paper is a continuation of [13] where nonlinear Schrödinger equations with repulsive (i.e. the minus sign in front of |x| −σ u) inverse-power potentials in the energy space were considered.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…the minus sign in front of |x| −σ u) inverse-power potentials in the energy space were considered. The local well-posedness (LWP) for (1.1) in the energy space H 1 was studied in [13]. More precisely, the author showed that (1.1) is locally well-posed in H 1 for both energy-subcritical and energy-critical cases.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have from [11,Proposition 4.7] (by taking V = 0 and W = |x| −b ) that the following interaction Morawetz inequality holds true for the defocusing problem (1.1) in dimensions N ≥ 3…”
Section: Acknowledgementmentioning
confidence: 99%